Photoinduced structural changes in As₁₀₀₋xSx layers - Stronski, A.; Vlcek, M.; Sklenar, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The present paper is concerned with investigations of photoinduced structural changes in As100-xSx layers. Optical constants of variously treated (virgin, exposed, annealed) samples were determined from optical transmission measurements in the spectral region 400-2500 nm. The energy dependence of refractive index n for variously treated samples was fitted by the Wemple-DiDomenico dispersion relationship and used to estimate the single-oscillator model parameters. It was found, that exposure, as well as annealing leads to the increase in n values over the all investigated spectral region. Compositional dependencies of single-oscillator model parameter Ed (dispersion energy), optical dielectric constant ε(0) show maximum at stoichiometric composition As₄₀S₆₀ and, possibly, weak maximum at As₂₈.₆S₇₁.₄ composition. Changes of the parameters of the single-oscillator model induced by treatment are discussed on the base of photo- and thermally-induced structural changes, which were directly confirmed by Raman scattering measurements. Such photoinduced structural changes provide good etching selectivity of As-S layers in amine based solvents. Intensity dependence of the Raman bands corresponding to the As rich and S rich molecular fragments on exposure time is well described by the exponential decay, which correlates with exponential decay dependence of the etching rate of As₁₀₀₋xSx layers on exposure.